KOMUNIKASI ORGANISASI DI DINAS KEPENDUDUKAN PENCATATAN SIPIL DAN KELUARGA BERENCANA DAERAH PROVINSI SULAWESI UTARA - WALONI, KRISTIN IREN; LENGKONG, FLORENCE; MAMBO, RULLY (Sam Ratulangi University, 2021)
This study aims to determine how organizational communication is in the Department of Population, CivilRegistration and Regional Family Planning, North Sulawesi Province. In this study using descriptive researchmethods with a qualitative approach. Based on the results of the research and discussion, the followingconclusions can be drawn, vertical downward communication, upward vertical communication, andhorizontal communication that are carried out discussing work matters, both in the form of coordinating work,working together, and sharing work. The type of communication used is formal and informal, but more oftenuses informal communication for daily communication, because it is more effective and efficient. Thecommunication method used is Informative and Persuasive, but more effective with the Informative method.The communication media used are oral, written, and electronic media, but it is more effective to use oralmedia. The communication barriers encountered are busy bosses, and busy boss schedules, so that it isdifficult for superiors to find subordinates who will carry out communication. Efforts are made by usingelectronic media to communicate, arrange time to meet with superiors, and wait for busy bossesKeywords: Communication, Organization, Media